2015
DOI: 10.1002/jqs.2808
|View full text |Cite
|
Sign up to set email alerts
|

A Marine Isotope Stage 4 age for Pleistocene raised beach deposits near Fethard, southern Ireland

Abstract: Citation for published item:qllgherD gF nd elferD wFF nd ¡ y gofighD gF @PHISA 9e wrine ssotope tge R ge for leistoene rised eh deposits ner pethrdD southern srelndF9D tournl of quternry sieneFD QH @VAF ppF USREUTQF Further information on publisher's website: httpXGGdxFdoiForgGIHFIHHPGjqsFPVHV Publisher's copyright statement: his is the epted version of the following rtileX qllgherD gFD elferD wF F nd ¡ y gofighD gF @PHISAD e wrine ssotope tge R ge for leistoene rised eh deposits ner pethrdD southern srelnd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
21
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 11 publications
(23 citation statements)
references
References 51 publications
2
21
0
Order By: Relevance
“…The Blackhall Till succeeds dated units of the Courtmacsherry Formation raised beach (Gallagher et al, 2015) and, therefore, was deposited in MIS 2. Hence, the Blackhall Till represents the earliest regional ice margin to have stabilised above the high RSL following the Last Glacial Maximum (LGM).…”
Section: Study Reach and Palaeoenvironmental Contextmentioning
confidence: 96%
See 4 more Smart Citations
“…The Blackhall Till succeeds dated units of the Courtmacsherry Formation raised beach (Gallagher et al, 2015) and, therefore, was deposited in MIS 2. Hence, the Blackhall Till represents the earliest regional ice margin to have stabilised above the high RSL following the Last Glacial Maximum (LGM).…”
Section: Study Reach and Palaeoenvironmental Contextmentioning
confidence: 96%
“…However, large engineering projects have revealed that the channel of the lower Suir is underlain by glaciofluvial deposits, up to 20 m thick, of clayey sands, gravels and boulders (Phillips et al, 2012). All Pleistocene glacigenic deposits in southeastern Ireland were laid down in the last glaciation (Warren, 1985;Gallagher and Thorp, 1997;Hegarty, 2004;O'Cofaigh et al, 2012;Gallagher et al, 2015) during Marine Isotope Stage (MIS) 2 (Lisiecki and Raymo, 2005: MIS 2, 14-29 ka;MIS 3, 29-57 ka;MIS 4, 57-71 ka). The glaciofluvial landforms of the Suir valley indicate that it was an arterial conduit for glacial meltwaters (Orme, 1964), which became confluent in Waterford Harbour with This article is protected by copyright.…”
Section: Study Reach and Palaeoenvironmental Contextmentioning
confidence: 99%
See 3 more Smart Citations